THE SIGNIFICANCE OF STEREOTYPES AND PREJUDICE IN CONFLICT RESOLUTION: THE CASE OF NORTH MACEDONIA (Religious dialogue and cooperation, 2022)
Stereotypes and prejudice have an important role in conflict resolution. Theyrepresent an underexplored sociological and psychological dimension of ethnic conflictsin the Western Balkans, and particularly in North Macedonia. Most research haveshownthat these are the root causes of interethnic conflict. Moreover, they are consideredthefuelof interethnic and interreligious conflict. The goal of this paper is to (1) present thegeneralrole of stereotypes and prejudices in intergroup conflict (be it ethnic or religious) conflictand (2) clarify and better understand their nature from socio-psychological perspectiveand (3) explore them on a small sample of140 Macedonian and Albanian children in North Macedonia in the municipalitiesofTetovo and Jegunovce. The research was conducted in February 2020, and HumanFigureDrawing projective technique was used in order to measure stereotypes andprejudice.The results are descriptive an indicate the actual situation in these two municipalities.Further, the findings show that Macedonian group of children could easily imagineanAlbanian as the `other` (friend) whereas the Albanian group of children couldeasilyimagine the `other` (friend) as someone who is not living in the state, not even inthesamemunicipality. This research findings recommend that more strategic and researchbasedapproach should be implemented in relation to minimizing the stereotypes andprejudiceamong Macedonian and Albanian children and improving interethnic coexistenceatgrassroot level.
Keywords: stereotypes; prejudice; conflict resolution; Macedonia